Predicting wear of ceramic–ceramic hip prosthesis using finite element method for different radial clearances. (December 2014) - Shankar, S.
Abstract : Hip replacement technique is widely used in replacing the femur head and acetabular cup by materials that are highly biocompatible. Such materials undergo surface wear due to post-operative activities that are experienced by the patients who undergo artificial hip replacement. Since wear is an important tribological phenomenon, it has to be minimised. Radial clearance plays a major role in lubricating the surface of materials which come into contact and also affects the wear rate considerably. In the present work, using three-dimensional (3D) physiological gait load for normal walking cycle as well as 3D rotation of ceramic femur head inside the ceramic cup, wear of bearing surfaces is calculated using finite element method for various radial clearance values. The simulation result is validated with the previous experimental observations, and they are found to be within the allowable range. Overall, the analysis revealed that there is a negligible change in volumetric wear rate, but the linear wear and contact pressure increases for higher radial clearances.